Educational Practice Evaluation of Teachers from Educational Centers: Indicators of improvement from the Inclusive Education - Asunción Lledó Carreres; Pilar Arnaiz Sánchez (Universidad Autónoma de Madrid, 2016)
Since the arrival to schools for pupils with disabilities in the process of change that led to the integration, the school has moved from resistance to change that the innovation project and the voices that many times, individually, have been addressing the different educational needs of their students because they are considered the responsibility of a faculty that still does not understand this so broad and complex as the diversity. This road has been long with many obstacles and hand of the obsolete pedagogy of homogeneity and exclusion. Although there is still some way to go, many teachers today we remain committed to finding solutions for change from the option of inclusive education. The present article can be a sign of that. This article describes the research conducted in schools in the province of Alicante during the academic year 2008/2009 and 2009/2010 with regard to aspects relating to qualifications of teachers and educational practices that underlie them, to analyze the processes of change and innovation taking place in schools to achieve an inclusive education. The aim has been to meet the demands of teacher training and the issues that favor or hinder since their beliefs, attitudes and aspects of training to implement inclusive practices. Drawing on the issues raised in this research and from the results and discussing them, we propose a series of general conclusions that can serve as a reflection to advance proposals for improving schools from the perspective of inclusive education.